2018
DOI: 10.26719/2018.24.7.664
|View full text |Cite
|
Sign up to set email alerts
|

Geographical inequality in cataract surgery among Iranians between 2006 and 2011

Abstract: To reduce this inequality, policy-makers should improve financial and physical access to cataract surgery, especially in the relatively deprived provinces, and tackle physician-induced demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the final section, this study recommends facilitating the accessibility of the required services for women, particularly those of reproductive age [25]. Other studies have found that regional disparity in Iran also occurs in cataract surgery services [26] and Iranian children and adolescents [27]. Regional differences in Iran may occur due to the unequal input of health resources between regions [28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…In the final section, this study recommends facilitating the accessibility of the required services for women, particularly those of reproductive age [25]. Other studies have found that regional disparity in Iran also occurs in cataract surgery services [26] and Iranian children and adolescents [27]. Regional differences in Iran may occur due to the unequal input of health resources between regions [28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…We estimated the LC and calculated the GI for the years 2000 and 2015 to ascertain any changes in inequality among countries for each selected development indicator. Many studies have applied these calculations to address levels of inequality in different disciplines (Yang et al 2019;Chowdhury et al 2018;Alinia et al 2018;Malakar et al 2018;Saez et al 2018;Stensrud and Valberg 2017). In this study, we use the cumulative percentage of a given indicator for each country to derive a global GI.…”
Section: Methodsmentioning
confidence: 99%
“…Current visual health guidelines in Peru do not adequately address the socioeconomic and health disparities in access to and utilization of eye care services (24)(25)(26). These differences in eye care can negatively impact older adults, reducing their quality of life, functional independence and increasing the risk of accidents (27)(28)(29)(30)(31). This study aimed to assess socioeconomic disparities in evaluating the vision of older adults with cataracts in Peru, looking at differences in accessing eye care services and treatment results.…”
Section: Introductionmentioning
confidence: 99%